Relationship between Sleep Deprivation and Daytime Sleepiness in different Groups of the Population: A Cross-sectional Study - Madeeha Akhlad; Hammad Ahmed Siddiqui; Muhammad Azharuddin (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Research consistently indicates that insufficient sleep, whether it is a persistent or short-term issue, can result in daytime sleepiness among the general population. Contributing factors include demanding work schedules, social commitments, and the habit of using electronic devices before bedtime. Aim: To find the relationship between sleep deprivation, daytime sleepiness, and socio-economic status, and their association among teachers, bachelor’s and master’s students, and medical practitioners. Materials and Methods: This cross-sectional study included the assessment of daytime sleepiness and quality of sleep among different populations using the Eppworth Sleepiness Scale (ESS) and the Pittsburgh Sleep Quality Index (PSQI), respectively. The socio-economic status was assessed using the modified Kuppuswamy Scale (mKS). The participants were categorised into three groups: teachers, students, and medical professionals according to their profession. In the analysis, to find the linear relationship between age, Body Mass Index (BMI), and the other three outcomes, Pearson’s correlation was used. Results: There were 65 (38.5%) males and 104 (61.5%) females among the respondents. On analysis, considering the overall results, it was found that there was a moderate positive correlation between age and BMI (r-value=0.232, p-value<0.05) and no significant correlation between age and ESS, PSQI, mKS. There was a moderately negative correlation between mKS and ESS (r-value=-0.205, p-value=0.016), suggesting that the lower the SES, the more the chances of daytime sleepiness in students’ group. In the teacher’s group, there was no significant correlation between age and BMI, ESS, PSQI, and mKS in any of the groups. Conclusion: It can be concluded that daytime sleepiness was related to socio-economic status in students, such that they are inversely proportional to each other. Medical practitioners experienced the most daytime sleepiness compared to other population groups.